2011
DOI: 10.2140/pjm.2011.249.343
|View full text |Cite
|
Sign up to set email alerts
|

Möbius isoparametric hypersurfaces with three distinct principal curvatures, II

Abstract: Using the method of moving frames and the algebraic techniques of T. E. Cecil and G. R. Jensen that were developed while they classified the Dupin hypersurfaces with three principal curvatures, we extend Hu and Li's main theorem in Pacific J. Math. 232:2 (2007), 289-311 by giving a complete classification for all Möbius isoparametric hypersurfaces in ‫ޓ‬ n+1 with three distinct principal curvatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…and therefore Möbius curvatures are finer than Lie curvatures. On a seemingly different thread, Hu, Li, and Wang [15,16,17] classified the hypersurfaces with vanishing Möbius form and constant Möbius principal curvatures, which are called Möbius isoparametric hypersurfaces, provided that the dimension of the hypersurface or the number of distinct principal curvatures is small. Until Rodrigues and Tenenblat [39] observed that an oriented hypersurface is a…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and therefore Möbius curvatures are finer than Lie curvatures. On a seemingly different thread, Hu, Li, and Wang [15,16,17] classified the hypersurfaces with vanishing Möbius form and constant Möbius principal curvatures, which are called Möbius isoparametric hypersurfaces, provided that the dimension of the hypersurface or the number of distinct principal curvatures is small. Until Rodrigues and Tenenblat [39] observed that an oriented hypersurface is a…”
Section: Introductionmentioning
confidence: 99%
“…Hence one easily derives Recall from [15,16,20], an immersed hypersurface is said to be a Möbius isoparametric hypersurface if its Möbius form vanishes and its Möbius principal curvatures are all constant.…”
mentioning
confidence: 99%
“…Since the publication of [23], the study of Möbius geometry of submanifolds in S n+p has made a lot of progress and many interesting results were obtained. Among them, we have the classification of submanifolds with particular Möbius invariants, such as the Möbius characterization of hypersurfaces with constant mean curvature and constant scalar curvature [17], the classification of Möbius isotropic submanifolds [10,19], the classification of Möbius isoparametric (respectively, Blaschke isoparametric) hypersurfaces with three distinct principal curvatures [11,14,15].…”
Section: Introductionmentioning
confidence: 99%